Global contagion and local response: the influence of centre–state relations and political culture in pandemic governance. Issue 3 (3rd July 2021) - Chatterji, Tathagata; Roy, Souvanic; Chatterjee, Atanu
ABSTRACT: Covid-19 has severely impacted lives and livelihoods in India. Faced with threatened livelihoods due to lockdowns in major cities, millions of poor informal sector workers have returned to their rural roots, provoking a complex intergovernmental problem that necessitates collective action but is plagued with a high degree of uncertainty. This article explores two interrelated issues. First, we examine the role of the central government in the Covid-19 crisis and the implications for centre–state relations. Second, we review the governance responses of two states, Kerala and Gujarat. We unpack how variations in political values and norms within which the key political actors of the two governing regimes are rooted had informed their policy priorities. We show how local political culture significantly affected critical decisions (e.g. emergency relief for the poor) and administrative implementation mechanisms (whether centralised or decentralised). We draw lessons on the influence of political culture in shaping pandemic governance response in a federal polity.